Integration of fillers in paint formulation: Comprehensive insights into methods, properties, and performance - Andrew Kasumba Buyondo; Hillary Kasedde; John Baptist Kirabira; Abdulfatah Abdu Yusuf (Results in Engineering)
The integration of fillers into paint formulations is crucial for enhancing mechanical, chemical, and aesthetic properties while lowering production costs. Despite their widespread use, challenges such as poor dispersion, compatibility issues, and environmental concerns remain significant. This review comprehensively examines the types, functions, preparation methods, and performance implications of fillers in paint formulations. The primary aim is to evaluate how natural, synthetic, and advanced fillers affect the rheological, mechanical, thermal, and aesthetic properties of paints, and to identify strategies for optimizing their use. Key findings indicate that optimized filler loading enhances rheology, UV resistance, and gloss retention without compromising adhesion or film integrity. For instance, incorporating 1–3 wt % nano-silica increased paint hardness by 30 %, while 20 wt % talc improved UV durability by 25 %. Furthermore, surface-treated fillers, such as silane-modified silica, enhanced dispersion and shelf stability, reducing sedimentation by up to 80 %. However, excessive loading beyond the critical pigment volume concentration (CPVC) leads to poor film formation and brittleness. Technical challenges, including inadequate dispersion, compatibility issues, and sedimentation, often compromise performance. Advanced processing techniques like high-shear mixing, surface treatment, and nano-modification are essential for overcoming these barriers. This review recommends adopting bio-based and recyclable fillers, standardizing characterization methods, and fostering stronger collaboration between industry and academia to develop next-generation functional fillers. Ultimately, optimizing filler selection and processing is critical for achieving high-performance, sustainable, and cost-effective paints that meet both industrial and environmental demands.